2019
DOI: 10.1109/access.2019.2939960
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Pattern Mining Suggests Wellbeing Supportive Behaviors

Abstract: Amidst the headlines about the attention economy and the possible impacts of screen time, research investigating the complex relationship between digital technology usage and wellbeing has gained urgency. Researchers generally use a combination of surveys and automatic tracking tools to gather time and frequency of technology use. However, the focus of data analysis has been on measuring duration and frequency of usage rather than exploring behavioral patterns, possibly better indicators of mood states or stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…This detection system has an accuracy of 70% and kappa score around 0.45. Further, our previous studies [12], [13] showed that digital footprints are also useful to predict mood. In this study, we attempted to explore if the mood prediction accuracy will be improved by adding lifestyle or physical context information.…”
Section: Related Workmentioning
confidence: 95%
See 4 more Smart Citations
“…This detection system has an accuracy of 70% and kappa score around 0.45. Further, our previous studies [12], [13] showed that digital footprints are also useful to predict mood. In this study, we attempted to explore if the mood prediction accuracy will be improved by adding lifestyle or physical context information.…”
Section: Related Workmentioning
confidence: 95%
“…In this study, the classifier is binary (positive and negative) because it will be the most useful to users: maximum possible accuracy but meaningful labels (similar to our previous studies [12], [13]). If we use more classes of mood, the mood detection system would have lower accuracy.…”
Section: Mood Detection Systemmentioning
confidence: 98%
See 3 more Smart Citations